Future directions in personality, occupational and medical selection: myths, misunderstandings, measurement, and suggestions - Ferguson, Eamonn; Lievens, Filip (Springer Verlag, 2017)
This paper has two objectives: (1) presenting recent advances in the personality field concerning the conceptualization of personality arising from the dynamic interactions of behaviour, biology, context, and states, and (2) discussing the implications of these developments for medical selection. We start by presenting evidence that traits are not longer regarded as deterministic and stable. Instead, they are found to change across generations, the life span, and in response to environmental contingencies. Next, drawing on recent research (behavioural reaction norms and the density distribution model) we posit how the expression of trait relevant behaviour changes depending on the situation, such that personality reflects both stability and plasticity across situations. Thus there is an urgent need to explore how traits change as function of medical education. Third, we demystify that some traits are better than others showing that so-called “good” traits have a dark-side. Fourth, we show how these developments impact on how personality might be assessed, thereby presenting recent evidence on the use of contextualized personality measures, Situational Judgment Tests, other reports, and implicit measures. Throughout the paper, we outline the key implications of these developments for medical selection practices.